2001
DOI: 10.1002/1098-1136(200102)33:2<131::aid-glia1012>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

S100b expression in and effects on microglia

Abstract: We evaluated the intracellular and extracellular biological role of S100B protein with respect to microglia. S100B, which belongs to the multigenic family of Ca2+-binding proteins, is abundant in astrocytes where it is found diffusely in the cytoplasm and is associated with membranes and cytoskeleton constituents. S100B protein is also secreted by astrocytes and acts on these cells to stimulate nitric oxide secretion in an autocrine manner. However, little is known about the relationship between S100B and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 0 publications
3
34
1
5
Order By: Relevance
“…Previous studies using primary microglia from newborn rat cortex or BV-2 microglial cell lines have demonstrated that micromolar to nanomolar concentrations of S100B cause IFNγ-induced expression of iNOS as well as NO secretion. 10,36 In contrast, our studies using BV2 and primary microglial cultures stimulated by LPS and/or IFNγ showed no effects of S100B on key markers of microglial activation, such as NO release or ROS production. Furthermore, it has been proposed that S100B may act through AGER and subsequently Toll-like receptors to induce inflammatory responses.…”
Section: S100b Does Not Influence Key Microglial Activation Markers Icontrasting
confidence: 72%
“…Previous studies using primary microglia from newborn rat cortex or BV-2 microglial cell lines have demonstrated that micromolar to nanomolar concentrations of S100B cause IFNγ-induced expression of iNOS as well as NO secretion. 10,36 In contrast, our studies using BV2 and primary microglial cultures stimulated by LPS and/or IFNγ showed no effects of S100B on key markers of microglial activation, such as NO release or ROS production. Furthermore, it has been proposed that S100B may act through AGER and subsequently Toll-like receptors to induce inflammatory responses.…”
Section: S100b Does Not Influence Key Microglial Activation Markers Icontrasting
confidence: 72%
“…To our knowledge, it is the first time that colocalization between a microglial and an astrocytic marker is observed in vivo. However, it has been reported earlier that primary microglial cell cultures as well as the BV-2 microglial cell line express S100b in vitro (Adami et al, 2001). As it appears associated with filamentous structures, it is purported that S100b protein might be involved in cytoskeleton remodeling in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…33 For example, microglia expresses the S100B protein which surrounds the phagosome of opsonized Cryptococcus neoformans, which in the presence of IFN-g stimulates transcription of the inducible NO synthase gene resulting in increased secretion of NO. 34 These cells express a greater number of PRRs, including TLRs and MHC II, allowing for increased communication with other immune cells through the secretion of cytokines and chemokines. 35 Nucleotide binding oligomerization domains-like receptors on microglia stimulate the production of IL-1b and IL-18 which assist in the recruitment of neutrophils into the CNS infection site.…”
Section: States Of Existencementioning
confidence: 99%